Global neodymium-hafnium isotope systematics - revisited - van de Flierdt, T; Goldstein, S; Hemming, SR; Roy, M; Frank, M; Halliday, A (2007)
Global Nd-Hf isotope systematics can be mainly described with two linear arrays, the global silicate Earth array ("the terrestrial array") and the global ferromanganese crust and nodule array ("the seawater array"). The offset between these two arrays provides evidence for the sources and mechanisms by which these elements are added to ocean water. However, the reason for this offset is under debate, with the two preferred hypotheses being (i) incongruent release of Hf during continental weathering and (ii) hydrothermal contribution of Hf to the seawater budget. Here we present new Nd and Hf isotope data on glacio-marine core-top sediments from around the perimeter of the Antarctic continent. The results range from εHf = - 30.0 to εHf = + 3.9 and εNd = - 21.3 to εNd = + 0.9, reflecting the large range of basement ages and lithologies around the Antarctic continent. In Nd-Hf isotope space, they confirm the systematic correlations found in rocks from other parts around the world and provide valuable insights into the previously underrepresented group of sediments with very old provenance. In this paper we revisit the cause for the offset of the seawater array from the terrestrial array using simple mass balance considerations. We use these calculations to test to what degree the seawater array could be a product of preferential weathering of "non-zircon portions" of the upper continental crust, implying retention of zircons in the solid residue of weathering. Lutetium-Hf and Sm-Nd evolution and mixing calculations show that the global seawater array can be generated with continental sources only. On the other hand, a predominantly hydrothermal origin of Hf in the ocean is not possible because the seawater Hf isotopic composition is significantly less radiogenic than hydrothermal sources, and requires a minimum fraction of 50% continental Hf. While hydrothermal sources may contribute some Hf to seawater, continental contributions are required to balance the budget. © 2007 Elsevier B.V. All rights reserved.